2013
DOI: 10.5433/1679-0359.2013v34n6supl2p4105
|View full text |Cite
|
Sign up to set email alerts
|

Características reprodutivas, de crescimento e idade ao primeiro parto em bovinos da raça Holandesa

Abstract: ResumoObjetivou-se neste trabalho analisar os componentes de eficiência reprodutiva, expressos pelas características, intervalo do primeiro para o segundo parto (IEP), número de serviços por concepção para o primeiro parto (NSC1), número de serviços por concepção para o segundo parto (NSC2), período de serviço (PS) e período de gestação (PG), além da idade ao primeiro parto (IPP) e desenvolvimento ponderal até os 15 meses de idade. Foram utilizados dados de 377 novilhas, de dois rebanhos, sendo um em Santa Cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
1
3
0
2
Order By: Relevance
“…Grebogi et al (2008) and Almeida et al (2017) found mean values of 390 and 110, and 420 and 61 days, for IP and PS respectively. However, they were like those found by Marestone et al (2013), who reported mean values of 449 (±118.2) and 178 (±118.73) days for Holstein cows in the states of São Paulo and Paraná, respectively. Such values are considered high for animals of this breed, in which the recommended values are approximately 365 days for IP and approximately 90 days for PS (Bahonar, Azizzadeh, Stevenson, Vojgani, & Mahmouudi, 2009).…”
Section: Table 5 Effect Of the Season On The Productivity And Milk Cosupporting
confidence: 88%
“…Grebogi et al (2008) and Almeida et al (2017) found mean values of 390 and 110, and 420 and 61 days, for IP and PS respectively. However, they were like those found by Marestone et al (2013), who reported mean values of 449 (±118.2) and 178 (±118.73) days for Holstein cows in the states of São Paulo and Paraná, respectively. Such values are considered high for animals of this breed, in which the recommended values are approximately 365 days for IP and approximately 90 days for PS (Bahonar, Azizzadeh, Stevenson, Vojgani, & Mahmouudi, 2009).…”
Section: Table 5 Effect Of the Season On The Productivity And Milk Cosupporting
confidence: 88%
“…, os quais tiveram médiade 24,31º C, 23,68º C e 22,19º C respectivamente. Segundo relatado por Guedes; Cunha e Lima (2017), a idade à primeira parição é uma medida da precocidade e da fertilidade das novilhas, além de estar diretamente ligada ao índice de crescimento do animal Marestone et al (2013). afirmaram que a idade ao primeiro parto de fêmeas bovinas varia de 24 a 30 meses.…”
unclassified
“…These numbers show an increase in the amount of produced milk and a reduction in the amount of milked cows, resulting in more efficient and productive animals, partially attributed to the adoption of biotechnologies allied to the genetical enhancement and activity management (Barkema et al, 2015;LeBlanc, 2010;Lucy, 2001;Ramírez-Rivera et al, 2019). Marestone (2013) states that the technologies applied to the agricultural field influence some factors, including reproductive efficiency, nutritional and sanitary factors, and estrus identification. These factors impact directly the productivity of the dairy cattle, besides their contribution to the delay in the return to ovarian activity in postpartum, consequently, with larger service time and intervals between calvings, reduction in lactation period, and lower production of calves per year and across cows lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Dairy producers look for high production and quality in milk as they are the characteristics that generate revenue and profitability on the farm. Marestone et al (2013) state that technologies applied to the agricultural environment influence some factors such as reproductive efficiency, directly impacting the productivity of the dairy herd. Elmetwally (2018) said reproductive problems contribute to the delay in the return to ovarian activity in the puerperium resulting in a longer service time and calving interval (CI), in addition to reduced lactation with lower production of calves per year per cow, for to have an efficient production in dairy farming is necessary to have a healthy reproduction.…”
Section: Introductionmentioning
confidence: 99%